Genetic environmental interaction to achieve optimum physiological states of crossbred cattle in tropical climate - A. Aryogi; L. Affandhy; D. Pamungkas; S. Setiasih; Y.N. Anggraeny; P.W. Prihandini; P.R. Matitaputty; I.N. Suyasa; S. Rusdiana; D.T. Ramsiati; W.I Wulansari; M. Chanafi; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Introducing crossbred cattle in both lowland and highland regions is anticipated to enhance the productivity of indigenous breeds. Tropical environments present challenges such as acclimatization problems and decreased productivity. This study aims to test the influence of the interaction between genetic factors (crossbred cattle and local breeds) and environmental factors. This study is unique in its contribution of valuable insights into the potential interplay between tropical climate conditions and the genetic makeup of crossbred cattle. It sheds light on how this interaction influences the physiological and reproductive capabilities of the cattle, as well as the alterations in reproductive hormone secretion within this specific population. The results will serve as the main consideration for the development of crossbred cattle in tropical climates.METHODS: A fully randomized design incorporating three variables was employed in this study: altitude (highland and lowland), cattle breed (crossbred and local), and observation time. The study involved 357 cattle: 116 crossbred in the lowland, 67 crossbred in the highland, 93 local breed in the lowland, and 81 local breed in the highland. The environmental conditions, physiological status, hormone concentration, and reproductive performance were all part of the observations. Data was gathered every other day during each month, except for the hormone data, which was collected based on the oestrus cycle. The enzyme-linked immunosorbent assay method was utilized to analyze hormone concentrations. The data was analyzed using factorial patterns with SPSS 26, with Duncan''s multiple-range test analysis.FINDINGS: The main finding of this study indicates that altitude influences the genetic traits of cattle relevant to the journal''s scope. Variations in altitude and breed significantly affect physiological parameters such as sweating rate, respiration, and pulse frequency, as well as hormone levels including follicle stimulating hormone and luteinizing hormone. Furthermore, reproductive metrics such as days open, service per conception, and calving interval are also impacted. The interaction between altitude, breed, and observation time, significantly affected physiological status, hormone concentration, and reproductive performances. In cattle with high body weight, the peak sweating rate occurs at 08:00 post meridiem – 02:00 ante meridiem (21.83-27.92 second per centimeter square); while the low body weight occurs at 12:00 ante meridiem – 06:00 ante meridiem (16.92-32.68 seconds per square meter). Crossbred cattle in lowland areas and at 02:00 ante meridiem – 02:00 post meridiem have the highest respiratory frequency (59.08-63.29 times per minutes), and during the day have the highest pulse rate (69.43 times per minutes). During peak estrus, crossbred cattle in highland areas demonstrate increased concentrations of follicle stimulating hormone (15.82 ng/mL) and luteinizing hormone (70.91 ng/mL). Crossbred cattle in the lowlands have longer days open (5.75 months), higher service per conception (1.62 times), and longer calving intervals (15.94 months).CONCLUSION:  Crossbred cattle reared in lowland settings may encounter a decline in both physiological and reproductive capabilities, while indigenous cattle have the ability to adapt, resulting in superior physiological and reproductive performance compared to crossbred cattle. The physiology and reproduction of cattle are shaped by genetic factors and the tropical environment, including 1) Genetic influence, 2). Adaptation to altitude and climate, 3) Stress zones and breed differences, 4) Body temperature, 5) Reproductive performance,6) Hormone concentrations. It is recommended that the development of crossbred cattle be carried out in the highlands.